The Impact of Leadership on School Improvement: An Analysis of Leadership Practices, Academic Performance and Engagement in Selected Private Schools in Dubai - EL AZIBI, AFAF ABDULHAMEED (2025)
Abstract This study investigates leadership practices in private schools in Dubai and their impact on student academic performance and engagement. The research used the thematic analysis of qualitative interviews with school leaders and teachers. Key leadership practices identified include training sessions, collaboration, fostering innovation and encouraging leadership roles. Through quantitative analysis, the study examines how these practices relate to survey and report data. The findings show that while some practices positively correlate with engagement, they may also present challenges, such as misalignments with academic priorities or inconsistent implementation. Cultural and institutional contexts significantly influence the effectiveness of these practices. The research provides valuable insights into leadership behaviours that either support or hinder student performance in the UAE context. The recommendations for school leaders focus on balancing the vision of the leaders, distributive practices, strategic leadership, culture and academic rigour for their effective implementation. The study also emphasises promoting feedback-driven actions and ensuring professional development is effectively implemented. Keywords: leadership, performance, engagement